Comprehension on doula's work at a maternity in Jequitinhonha Valley - MG - Patrícia de Oliveira Lima; Marcos Luciano Pimenta Pinheiro; João Luiz de Miranda; Helisamara Mota Guedes; Herlon Fernandes de Almeida
Abstract Objectives: to analyze the understanding of puerperae, doulas and the care team about the presence of a doula during the pregnant women's parturition process. Methods: this is a qualitative study, using semi-structured interviews as a data collection instrument. The saturation criterion was used to limit the sample and proceed to the Content Analysis. Results: 19 participants were interviewed, 10 were the health team, 5 were doulas and 4 were puerperae. After the analysis, three categories were identified: the doula's presence during the pregnant women's labor and their meaning, the doula's follow up during the pregnant women's labor and its improvements, the influence of doulagem in the academic formation. The presence of doulas brought to the parturient security, support, humanization and follow-up on childbirth process. The team brought comfort and tranquility.The doulas scored benefits for academic training. Conclusions: it was possible to recognize doula as part of the humanized care, to provide subsidies for a reflection of her work, and to reveal the influence of the practice of doulagem for academic formation of doulas at university.